Fishing for social realities - challenges to sustainable fisheries management in the Cape Horn Biosphere Reserve - Pollack, G.; Berghöfer, Augustin; Berghöfer, Uta (Marine Policy, 2008)
Social-ecological complexity challenges conservation-oriented interventions even in settings with a small number of actors and conflicts involved. This article examines the development and trajectory of King and Snow Crab fisheries in the Cape Horn Biosphere Reserve (BR), the highly remote but globally connected Southern tip of the Americas. The feasibility of the Chilean legal instrument of Marine Management Areas (MMA) is assessed as a tool for mitigating impacts of overfishing in the area. Examining the local fishers' perspectives in complement to a context analysis we find that external management models such as the MMA are not suited to make Cape Horn fisheries sustainable. Instead, efforts should be dedicated to a continuous process of stakeholder collaboration for developing site-specific management concepts and structures. These should be embedded in the larger BR initiative. Considering the area's particular conditions, several recommendations for such a process are formulated.